Young athletes upper knee muscular strength isokinetic testing - Ðukic, B.; Mirkovic, M.; Vujanovic, S.; Strajnic, B. (Sports Science and Health, 2019)
This research main goal is to determine differences in maximum upper knee musculature torque moment of judo, football and handball players. For the needs of the research, 30 respondents were tested, of which 10 were football, 10 handball players and 10 judo athletes. Testing was conducted in Isokinetic Diagnostic Cabinet of the Provincial Institute for Sports and Sports Medicine in Novi Sad on the isokinetic dynamometer "Easytech prima DOC". Signifi cant differences were noted in the maximum torque moment of both legs extensors force (PTQR, PTQL) between judo athletes and football players, in favor of judo. Obtained results between observed groups can be attributed to the various sports branches training processes specifi cities, i.e. performing certain techniques in the sport itself.